Analisis Urgensi Kewenangan Notaris Dalam Mensertifikasi Transaksi Secara Elektronik - Adelia Puspitasari; Eko Wahyudi (Pusat Riset dan Inovasi Nasional, 2023)
Online transactions know no boundaries, just use a smartphone or computer connected to the internet so that everyone can search and find what they want. Electronic transactions involving Notaries can be seen in the elucidation section of Article 15 paragraph (3) of Law Number 2 of 2014 concerning the Position of Notary, Notaries have the authority to certify transactions conducted electronically. Cyber Notary has the main function of certifying and authenticating electronic transaction activities. Cyber notary is the concept of utilizing technological developments used by Notaries in carrying out their duties and authorities, such as document digitization, electronic signing of deeds etc. Even though it is stated in the Elucidation of the Notary Office Law, there is still confusion in meaning, a question arises that needs to be studied from this problem, namely how the implementation of electronic transaction certification is carried out by a Notary.